The imprint of another life : adoption narratives and human possibility - Homans, Margaret, 1952- (The University of Michigan Press, 2013)
The author, a literary scholar, examines fiction-making's special relationship to themes of adoption, an "as if" form of family making, fabricated or fictional instead of biological or "real." Adoption has tended to generate stories rather than uncover bedrock truths. Adoptive families are made, not born; in the words of novelist Jeanette Winterson, "adopted children are self-invented because we have to be." In attempting to recover their lost histories and identities, adoptees create new stories about themselves. While some believe that adoptees cannot be whole unless they reconnect with their origins, others believe that privileging biology reaffirms hierarchies (such as those of race) that harm societies and individuals. Adoption is lived and represented through an irresolvable tension between belief in the innate nature of human traits and belief in their constructedness, contingency, and changeability. The book shows some of the ways in which literary creation, and a concept of adoption as a form of creativity, manages this tension. The book addresses a series of questions about common beliefs about adoption. Underlying these beliefs is the assumption that human qualities are innate and intrinsic, an assumption often held by adoptees and their families, sometimes at great emotional cost. This book explores representations of adoption - transracial, transnational, and domestic same-race adoption - that reimagine human possibility by questioning this assumption and conceiving of alternatives. This book engages in debates within adoption studies, women's and gender studies, transnational studies, and ethnic studies; it will appeal to literary scholars and critics, including specialists in memoir or narrative theory, and to general readers interested in adoption and in race. -- Provided by publisher.